Nickel: humoral and periodontal changes in orthodontic patients - Leandro Silva Marques; Camila Alessandra Pazzini; Mariele Cristina Garcia Pantuzo (Dental Press Editora, 2012)
INTRODUCTION: Although several studies have discussed nickel influence on the development of immunological reactions in orthodontic patients, it is noticed that the evidence towards the appliances, as well as towards the possible consequences of this material on the oral and general health of the individual are still inconsistent. OBJECTIVE: The aim of this article is to present the current stage of knowledge on this issue, highlighting the most recent findings considering the periodontal and humoral aspects of allergic subjects.